2011
DOI: 10.3354/dao02345
|View full text |Cite
|
Sign up to set email alerts
|

Lacaziosis and lacaziosis-like prevalence among wild, common bottlenose dolphins Tursiops truncatus from the west coast of Florida, USA

Abstract: Lacaziosis (lobomycosis; Lacazia loboi) is a fungal skin disease that naturally occurs only in humans and dolphins. The first reported case of lacaziosis in a bottlenose dolphin Tursiops truncatus occurred in 1970 in Sarasota Bay, Florida, USA, and subsequent photo-ID monitoring of the Sarasota Bay dolphin population has revealed persistence of the disease. The objectives of this study were to estimate lacaziosis prevalence (P) in 2 bottlenose dolphin populations on the west coast of Florida (Sarasota Bay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Although limited for determining skin disease causes, photo-id data provide a relatively inexpensive and non-invasive means of assessing body and skin condition [13], as well as lesion progression, recurrence, or resolution [9], [14], [15] for free-ranging marine mammal populations. Other studies have relied on by-catch or stranding data [1], [4], [5], [9], [16], [17], or capture-release health assessment data [3], [18], [19] to estimate disease burden in wild populations; however, these methods can be limited by small sample sizes or in the case of stranding data, biased towards individuals with compromised health [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although limited for determining skin disease causes, photo-id data provide a relatively inexpensive and non-invasive means of assessing body and skin condition [13], as well as lesion progression, recurrence, or resolution [9], [14], [15] for free-ranging marine mammal populations. Other studies have relied on by-catch or stranding data [1], [4], [5], [9], [16], [17], or capture-release health assessment data [3], [18], [19] to estimate disease burden in wild populations; however, these methods can be limited by small sample sizes or in the case of stranding data, biased towards individuals with compromised health [20].…”
Section: Introductionmentioning
confidence: 99%
“…This could be related to influx of terrestrial pollutants (Woodward-Clyde Consultants 1994) in ecosystems sustaining enclosed bodies of water with freshwater influx, leading to variations in temperature, tides anaerobic sediment conditions, and salinity levels. Salinity could also be involved in dermal lesions in re sident inshore cetaceans (Wilson et al 1999, Murdoch et al 2008, Burdett Hart et al 2011. Another aspect to be considered is the fact that offshore animals are rarely examined in comparison to inshore animals.…”
Section: Discussionmentioning
confidence: 99%
“…This led to an elevation in calculated cases during the study period reported in the publication. For instance, a peak in the number of fungal calculated cases in 2003 resulted from a single publication that estimated prevalence of lacaziosis in a study population over two years [ 34 ]. This reflects a short period of reporting of endemic chronic skin lesions present in other years, rather than an outbreak of fungal cases in the southeast U.S. in those two years.…”
Section: Discussionmentioning
confidence: 99%